PEMANFAATAN LIMBAH KULIT UDANG VANNAMEI MENJADI PUPUK ORGANIK CAIR SEBAGAI UPAYA PENGELOLAAN LIMBAH TAMBAK DI DESA LABUHAN LOMBOK - Hidayat Hidayat; Rizky Ananda; Manda Eka; Kurniawan Kurniawan; Alwi Saputra; Yuliana Asri; Awan Darmawan; Zaenal Abidin (Jurnal Pepadu, 2026)
Whiteleg shrimp farming in Labuhan Lombok Village, Pringgabaya District, East Lombok Regency, contributes significantly to the local economy but also generates shrimp shell waste that has not been optimally utilized. The accumulation of this waste may cause environmental problems, particularly unpleasant odours and an increased fly population around pond areas. This community service program aimed to utilize whiteleg shrimp shell waste as liquid organic fertilizer (LOF) while improving community knowledge of sustainable aquaculture waste management. The program involved field observation, coordination with pond owners, preparation of tools and materials, LOF production, education, and program evaluation. The fertilizer was produced using 500 g of shrimp shell waste, 100 mL of EM4 Agriculture, 100 mL of molasses, and 5 L of rice-washing water, followed by fermentation for 10–15 days. Educational activities were delivered to 10 pond workers through presentations, demonstrations of LOF production, and discussions. Evaluation was conducted using pre-tests and post-tests, product quality observations, participant participation levels, and program sustainability potential. The results showed that the LOF was successfully produced with a yellowish-brown colour, a characteristic fermentation aroma, and no foul odour. The educational activity improved participants’ understanding of shrimp shell waste management, as reflected in the post-activity evaluation results and active participation during the program. The application of LOF to chili plants also showed improved growth responses, indicated by broader leaves, stronger stems, and healthier plant appearance. This program demonstrates that converting whiteleg shrimp shell waste into liquid organic fertilizer is an environmentally friendly and value-added alternative for aquaculture waste management that may support sustainable agriculture in Labuhan Lombok Village.